Inhibition of mPGES-1 or COX-2 Results in Different Proteomic and Lipidomic Profiles in A549 Lung Cancer Cells - Bergqvist, Filip; Ossipova, Elena; Idborg, Helena; Raouf, Joan; Checa, Antonio; Englund, Karin; Englund, Petter; Khoonsari, Payam Emami; Kultima, Kim; Wheelock, Craig E.; Larsson, Karin; Korotkova, Marina; et al. (Frontiers in Pharmacology, 2019)
Pharmacological inhibition of microsomal prostaglandin E synthase (mPGES)-1 for selective reduction in prostaglandin E2 (PGE2) biosynthesis is protective in experimental models of cancer and inflammation. Targeting mPGES-1 is envisioned as a safer alternative to traditional non-steroidal anti-inflammatory drugs (NSAIDs). Herein we compared the effects of mPGES-1 inhibitor Compound III (CIII) with the cyclooxygenase (COX)-2 inhibitor NS-398 on protein and lipid profiles in interleukin (IL)-1β induced A549 lung cancer cells using mass spectrometry. Inhibition of mPGES-1 decreased PGE2 production and increased PGF2α and thromboxane B2 (TXB2) formation, while inhibition of COX-2 decreased the production of all three prostanoids. Our proteomics results revealed that CIII downregulated multiple canonical pathways including eIF2, eIF4/P70S6K, and mTOR signaling, compared to NS-398 that activated these pathways. Moreover, pathway analysis predicted that CIII increased cell death of cancer cells (Z=3.8, p=5.1E-41) while NS-398 decreased the same function (Z=-5.0, p=6.5E-35). In our lipidomics analyses, we found alterations in nine phospholipids between the two inhibitors, with a stronger alteration in the lysophospholipid (LPC) profile with NS-398 compared to CIII. Inhibition of mPGES-1 increased the concentration of sphinganine and dihydroceramide (C16:0DhCer), while inhibition of COX-2 caused a general decrease in most ceramides, again suggesting different effects on cell death between the two inhibitors. We showed that CIII decreased proliferation and potentiated the cytotoxic effect of the cytostatic drugs cisplatin, etoposide, and vincristine when investigated in a live cell imaging system. Our results demonstrate differences in protein and lipid profiles after inhibition of mPGES-1 or COX-2 with important implications on the therapeutic potential of mPGES-1 inhibitors as adjuvant treatment in cancer. We encourage further investigations to illuminate the clinical benefit of mPGES-1 inhibitors in cancer.